(Re)educating the senses to multicultural communities: prospective teachers using digital media and sonic cartography to listen for culture. (3rd July 2017) - Brownell, Cassie J.; Wargo, Jon M.
Abstract: Attuning to the acoustic ecologies of multicultural education, this critical qualitative project interrogated how elementary prospective teachers (PST) used digital media to write community through and with sound. Examining PST produced soundscapes and the practice of sonic cartography, this study inquired how hearing difference and listening to community re-educated the senses towards issues of difference, belonging, and multiculturalism. Findings illuminate three ways in which PSTs maintained a 'proper distance' – a proximal, reflexive, and reciprocal stance – through digitally composing their cartographic creations and reflections. Developing materials that hear and sustain community, this study has implications for how English educators can attune to the frequencies and rhythms of culture while designing towards more equitable landscapes for learning.